Dukes’ B 병기의 대장암 환자에서 Cytokeratin-19 항체를 이용한 림프절 미세전이의 발견 - 신응진(Eung Jin Shin); 김형철(Hyung Chul Kim); 임철완(Chul Wan Lim); 조규석(Gyu Seok Cho); 주종우(Chong Woo Chu); 백무준(Moo Joon Baek); 박내경(Nae Gyung Park); 장용석(Yong Seok Jang); 김재준(Jae Joon Kim); 송옥평(Ok Pyung Song); 이민혁(Min Hyuk Lee) (Annals of surgical treatment and research, 2004)
Purpose: The aims of this study were to immunohistochemically identify lymph node micormetastases in Dukes' B colorectal cancer patients, and determine the relationship between lymph node micrometastases and other prognostic factors and recurrence rates. Methods: A retrospective analysis was conducted of 990 lymph nodes from Dukes' B 42 patients who had undergone radical colorectal resection. These lymph nodes were immunohistochemically examined with monoclonal antibodies against cytokeratin-19. The prognostic factors and recurrent rates were compared between patients with and without lymph node micrometastases. Results: Micrometastases were confirmed in 19 nodes (1.9%) from 9 patients (21.4%). No correlations were observed between micrometastases and the prognostic factors, with the exception of the preoperative CEA level. 8 of the 9 (88.9%) patients with micrometastases had preoperative CEA levels significantly elevated above 5 ng/ml (P＜0.0001). There were no significant differences in the recurrent rates (P=0.0572) between patients with and without micrometastases during the short term follow up period (14.8 months) at the 95% confidence interval, but there were significant differences at the 90% confidence interval. Conclusion: High preoperative CEA levels increase the risk for micrometastases, and the presence of micrometastases might increase the possibility of recurrence. Thus, a routine immunohistochemical technique for identifying micrometastases is recommended in the patients with a high preoperative CEA level. However, a more definite clinical significance of lymph node micrometastases awaits further extensive prospective studies. KCI Citation Count: 0